Stroke Exacerbates Cancer Progression by Upregulating LCN2 in PMN-MDSC - Huang, Tingting; Li, Yan; Zhou, Yuxi; Lu, Bingwei; Zhang, Yueman; Tang, Dan; Gan, Yu; He, Zhengzhou; Chen, Zengai; Yu, Weifeng; Li, Peiying (Frontiers in Immunology, 2020)
Acute ischemic stroke（AIS）is common in patients with cancer, and mounting clinical evidences suggests that it may shorten the survival of cancer patients. But how stroke affects the progression of cancer remains unclear. We inoculated B16 tumor cells (2 × 105) subcutaneously before distal middle cerebral artery occlusion (dMCAO) or sham surgery in C57BL/6 mice and found that compared to sham operated mice, dMCAO mice developed significantly increased tumor volume and were accompanied by lower survival rate. To explore the underlying mechanism, we performed RNA-sequencing analysis of the tumor tissue from mice with or without stroke and found prominent upregulation of lipocalin 2 (LCN2) in the tumor from stroke mice compared to those from sham mice. Using quantitative reverse transcription-PCR, we confirmed increased mRNA expression of LCN2 as well as anti-inflammatory cytokines-Arg1, IL-10, and decreased mRNA level of pro-inflammatory cytokines-IL-6, IL-23 in the tumor of cancer-bearing stroke mice. Both immunofluorescence staining and flow cytometry analysis revealed that increased expression of LCN2 was mainly derived from the PMN-MDSCs in the tumor. We also found that stroke reduced the PMN-MDSCs in the peripheral blood, but increased PMN-MDSCs in the tumor of the cancer-bearing mice after stroke. In conclusion, cerebral ischemic stroke may exacerbate cancer progression by increasing LCN2 expression in PMN-MDSCs, which turns out to be a promising therapeutic target to suppress cancer progression after ischemic stroke.